The Influence of Physical and Psychological Quality on the Performance of Sports Dance - Bo Ren, (Revista de Psicología del Deporte (Journal of Sport Psychology), 2023)
Sports dance-specific physical fitness training can improve sports dance players' physical posture and performance abilities while enhancing their overall quality. This study is conducted to ascertain the effect of physical and mental health on sports dance performance. This research analyzes 20 outstanding sports dance athletes who have won the top five national sports dance competitions, the top three provincial sports dance competitions, and the top three group sports dance competitions, as well as 20 renowned sports dance experts, teachers, and coaches. The research indicates that the combination of physical and psychological qualities directly impacts the performance of sports dance. This study uncovered novel findings and concluded that general physical fitness and special physical fitness must be clearly defined in the physical fitness training strategy, and targeted training must be performed. After considering both their practical and theoretical implications, the findings of this study have some limitations. Future studies should resolve these limitations.